Nepal's investment climate: Leveraging the private sector job creation and growth. - Banskota, Mahesh (Nepal Tourism and Development Review, 2013)
DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7386 Nepal Tourism and Development Review Vol.2(1) 2012 160-167